Tight binding description of the electron-phonon and spin-phonon interactions in electron transfer in DNA - Feijoo Valarezo, Steven Andrés (2022)
The unique structure of DNA is bound to the wide range of interesting properties this molecule has shown. Lately, the electronic properties of this molecule raised attention in the field of spintronics, specifically, the ability to act as a spin-filter. Nevertheless, the mechanism that controls this behavior is yet to be clarified; and in fact other properties such as conduction were experimentally tested, and while in some experiments it was observed that DNA acted as insulator, others observed semiconductor, conductor or superconductor behaviors. As an effort to continue this line of investigation and discover how to make new devices using DNA, this work tries to describe its electron transfer based on $π$ orbitals on the B-form of this molecule by considering phonon and spin effects, which are present in physiological conditions where applications are most important. Using the two center approximation, the Envelope function, smoothing function, and the Tight Binding (TB) approach; two models were developed to study electron transfer (ET) in DNA. It was found that phonons have both relevance in intra and inter-helix ET, while spin-phonon interaction is found only intra-helix with spin-flip coupling. Optical phonons are coupled to electrons at first order while acoustic ones only couple to second order, thus optical modes are much more relevant. Intra-helix coupling with no spin-flip yields only a second order kinetic term thus the phonon and spin interactions don't affect this coupling. In conclusion, the model was able to make predictions qualitatively describing the persistence of coherence implied in experiments.